2020
DOI: 10.2298/tsci181027106m
|View full text |Cite
|
Sign up to set email alerts
|

Suspended nanoparticles on mixed convection flow of a Jeffrey fluid due to a horizontal circular cylinder with viscous dissipation

Abstract: The non-Newtonian Jeffrey fluid model describes the viscoelastic property that elucidates the dual components of relaxation and retardation times. Nonetheless, there has been considerable attention on its unsatisfactory thermal performance. The model of nanofluid is contemporarily in the limelight due to its superior thermal performance compared to the conventional fluid. The proposed study herein aims to examine the Jeffrey nanofluid model over a horizontal circular cylinder with mixed convection flow. The fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…y Also, we found that Eqs. (12) to (15) can be reduced to the mixed convection Newtonian fluid as reported by Mohamed et al, [36], provided the absence of the Jeffrey fluid…”
Section: Mathematical Formulationmentioning
confidence: 74%
See 1 more Smart Citation
“…y Also, we found that Eqs. (12) to (15) can be reduced to the mixed convection Newtonian fluid as reported by Mohamed et al, [36], provided the absence of the Jeffrey fluid…”
Section: Mathematical Formulationmentioning
confidence: 74%
“…The non-linear PDEs (Eqs. (12) to (14)) with the respective boundary conditions (Eq. (15)) are treated through the Keller-box method.…”
Section: Resultsmentioning
confidence: 99%
“…The model of non-Newtonian Jeffrey fluid is known for its ability to describe viscoelastic property, namely the dual components of retardation and relaxation times [44]. There are three articles that used Jeffrey Nanofluid and all of them are produced by Zokri et al, [44][45][46]. Two of them are based on Buongiorno model and the other one is based on Tiwari and Das model.…”
Section: Jeffrey Nanofluid (Buongiorno and Tiwari And Das)mentioning
confidence: 99%
“…This framework empowers researchers and engineers to comprehend and predict the flow characteristics of such fluids in diverse scenarios. Mohd et al [22] studied the behavior of suspended nanoparticles within the context of mixed convection flow of a Jeffrey fluid induced by a horizontal circular cylinder, considering the effects of viscous dissipation. Recently, Raje et al [23] investigated the entropy generation associated with the flow of Jeffrey fluid through an inclined pipe of circular cross-section, taking into account the presence of a uniform porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Mohd et al. [22] studied the behavior of suspended nanoparticles within the context of mixed convection flow of a Jeffrey fluid induced by a horizontal circular cylinder, considering the effects of viscous dissipation. Recently, Raje et al.…”
Section: Introductionmentioning
confidence: 99%